The Relationship between Islamic Religious Education and the Formation of Morals in Students - Muhammad Hilmy; Mukhammad Bakhruddin; Muhammad Fazlurrahman Hadi (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Family, community and government, through guidance, teaching, and training activities, which take place in school and out of school for life, the aim is to be able to help in life and improve and optimize their potential and talents. The study aims to determine how the condition of Islamic religious education and moral formation in students at SMK Negeri 2 Surabaya. The research design uses a quantitative research approach with a descriptive correlational method. The results of this study found that the results of the simple linear regression test have proven that there is an influence between Islamic religious education and student character using the results of calculations that have been made to get a linear regression value Y = 49.116 + 0.108X1 + e, sig. Level 0.000 <0.05 (alpha value), the conclusion is that there is an influence between Islamic religious education and student character and the test results of the coefficient of determination (R2) obtained the coefficient of determination (R square) = 0.782. This means that 78.2% of student character formation variables can be explained by the influence of Islamic religious education while the remaining 28.2% is explained by other variables not proposed in this study.